Disruptions to U.S. local public health's role in population-based substance use prevention and response during COVID-19 - Kellie Hall; Francis Higgins; Karla Feeser Beach; Kabaye Diriba; Mandy Sladky; Timothy C. McCall (BMC, 2022)
Abstract Background COVID-19 dramatically limited the scale and scope of local health department (LHD) work, redirecting resources to the response. However, the need for essential public health services-including substance use prevention-was not reduced. Methods We examined six quantitative data sources, collected between 2016 and 2021, to explore the impact of the COVID-19 pandemic on LHD substance use-related services. Results Before the pandemic, the proportion of LHDs providing some level of substance use prevention services was increasing, and many were expanding their level of provision. During the pandemic, 65% of LHDs reduced their level of substance use-related service provision, but the proportion of LHDs providing some level of services remained steady from prior to COVID-19. Conclusion We discuss policy recommendations to mitigate the risk of service disruptions during future public health emergencies, including direct and flexible funding for LHDs and federal directives declaring substance use prevention services as essential.